ACADEMIC VOCABULARY MASTERY AND PERCEPTION FOR EFL STUDENTS OF UNIVERSITAS BINA DARMA - Cita Hikmah Yanti (HOLISTICS, 2018)
This study aims to investigate the essential and unsolved issue during English learning in tertiary level. Unlike in high school, English is taught by using common lexicon and the students are required to communicate actively with uttered everyday conversation. Meanwhile, the vocabulary they received during their previous education failed to help them in further education. The writer assumed the fact that academic vocabulary mastery becomes the major problem in their comprehension in understanding academic articles, journal and research. Through this study, the writer found out that 50 students from English study program were on the unsatisfied level in the academic vocabulary mastery. About 76,3% respondents were on the poor to good level and around 23,7% were on the level good to very good. However, none of them is able to be on the excellent level of vocabulary mastery. Furthermore, the students’ attitude towards the aspect of academic vocabulary mastery showed positive responds. They dominantly affirmed that Academic vocabulary help them understand better in reading academic papers. The knowledge of the academic vocabulary will build their confidence in their ability to read academic material and identify the important points in academic material better. Mastery in academic vocabulary considered very important for students to read more effectively, help them review lecture notes and do skimming and scanning more effectively in learning independently during their tertiary level education.